Persfektif Hukum Terhadap Tindak Pidana Penistaan Agama - Romi Napitupulu (CV. Rayyan Dwi Bharata, 2025)
This paper examines the interpretation of the crime of religious blasphemy as defined by grammatical interpretation and meaning in Indonesian positive law. Background case of religious defamation by Basuki Tjahaja Purnama or Ahok. with the decision of No.1537Pid.B / 2016 / PN. Jkt Utr. In that case there is a phrase